Landscape of clinical trials in cancer cachexia: assessment of trends from 1995–2024 - Ana Regina Cabrera; Kaitlyn Parker; Deena B. Snoke; Bart Hammig; Nicholas P. Greene (BMC Cancer)
Abstract Background Cancer cachexia, a multifactorial syndrome characterized by unintentional weight loss, is a frequent complication of cancer that impacts patients’ quality of life and survival. Methods In this retrospective review, we evaluated the landscape of clinical trials registered on ClinicalTrials.gov for the consideration of potential factors contributing to biological human heterogeneity in their design and analyses. Results Among clinical trials registered from 1995–2024, we observed increased inclusion of female participants, but lack of reporting of sex as a biological variable. The majority (~ 93%) of participants were of Caucasian descent. There was a substantial divergence in the diagnostic criteria and a wide range of tools employed to measure cancer cachexia. Lastly, few studies considered cancer type and stage as clinical variables. Conclusion Overall, a substantial gap remains in our knowledge of cancer cachexia in non-white individuals and in females. Ultimately, these underreported data across cancer cachexia clinical trials complicate the comparison and interpretation of clinical trials results, both in the broader human population and in specific cancer types. The current evolution of knowledge and new methodologies used for cancer cachexia assessment reinforce the need for a constant revision of the consensus definition and diagnosis criteria to align with current advances in our understanding of human heterogeneity in cancer cachexia. Graphical Abstract